THE EFFECTIVENESS OF GROUP GUIDANCE WITH PROBLEM SOLVING AND SELF-MANAGEMENT TECHNIQUES TO IMPROVE SELF-EFFICACY - Hananto, Ipung; Eddy Wibowo, Mungin; Wagimin, Wagimin (Jurnal Bimbingan Konseling, 2020)
This study was intended to obtain empirical data on the extent of group guidance with problem solving and self-management techniques to improve the self-efficacy of SMP Negeri 34 Semarang students. To do so, the researchers employed experimental method with pretest posttest design, and involved 27 students of SMP Negeri 34 Semarang selected using purposive sampling technique. The results showed that the group guidance with problem solving and self-management techniques were able to improve the self-efficacy of SMP Negeri 34 Semarang students. Further, the implication of the findings of this study are presented in the discussion chapter.